Future Narratives: Theory, Poetics, and Media-Historical Moment - Bode, Christoph (De Gruyter, 2013)
This head volume of the ´Narrating Futures` series defines and identifies Future Narratives. It parses their characteristic features and aims at an abstract classification of the whole corpus, irrespective of its concrete manifestations across the media. Drawing on different theorems and approaches, it offers a unified theory and a poetics of Future Narratives. Locating the media-historical moment of their emergence, this volume paves the way for the following volumes, which deal with how Future Narratives are refracted through different media.